6-phytase and/or endo-β-xylanase and -glucanase reduce weaner piglet´s diarrhea and improve bone parameters - Brandão Melo, Antonio Diego; de Oliveira, Angela Cristina da Fonseca; da Silva, Paola [UNESP]; os Santos, Jeanne Borosch; de Morais, Rafaela; de Oliveira, Geovane Rosa; Wernick, Bruno; Carvalho, Paulo Levi de Oliveira; Artoni, Silvana Martinez Baraldi [UNESP]; Costa, Leandro Batista (Elsevier, 2020)
The present study evaluated the effect of a 6-phytase of bacterial origin (NatuphosⓇ E) alone or with a carbohydrase combination (NatugrainⓇ TS) dietary supplement for weaned piglets on growth performance, diarrhea incidence, and bone parameters. One hundred forty-four weaned piglets were assigned to six treatments with eight replicates per treatment, using a randomized block design. The study lasted 42 d. The treatment diets were: T1 - a control based on corn and soybean meal, meeting all nutrient requirements for weaned piglets; T2 - reduced calcium (Ca), phosphorus (P), metabolizable energy (ME) and amino acids content; T3 - T2 diet + an additional reduction of ME; T4 - T2 + 500 FTUs/kg of feed; T5 - T2 + 1000 FTUs/kg of feed; T6 - T3 + 500 FTUs/kg of feed + 100 g of a carbohydrase combination (5,600 TXU.g−1 and 2,500 TGU.g−1)/ton of feed. The statistical analysis was separated into three sets of comparisons: 1) T1, T2 and T3 and 2) T1, T3 and T6, both of which were submitted to ANOVA and, when P<0.05, the means were compared by Dunnett's test; and 3) T1, T2, T4 and T5, which were submitted to ANOVA and, when P<0.05, the means were compared by the Tukey's test. A Chi-square test (X²) was used to compare the diarrhea incidence between treatments, using the same sets mentioned above. There was no difference (P˃0.05) between the treatments on growth performance and feed efficiency. In general, higher diarrhea incidence (P˂0.05) was observed in T2 than T1, while T1 was similar (P˃0.05) to T3 at 1 to 42 d of the experiment. The composition of ash, Ca and P in bone was reduced in T2 and T3 compared to T1. However, piglets fed with 500 FTUs/kg of feed without or with carbohydrase (T4 and T6) or 1000 FTUs/kg of feed (T5) presented lower (P˂0.05) diarrhea incidence, improved bone mineral composition and bone densitometry than the diets with reduced nutritional specifications (T2 and T3) and similar values to the T1 control. Phytase, with or without carbohydrase additions, in diets for weaned piglets with reduced nutritional levels can increase nutrient uptake, reduce diarrhea incidence and improve bone parameters, without affecting growth performance.
Keywords: Bone mineral density; Diarrhea; Enzymes; Nutrition; Piglets